Simulation for determining the rod pump system parameter values using finite difference method - Erwani Merry Sartika; Arief Darmawan (Institute of Advanced Engineering and Science, 2021)
Lifting petroleum to the surface requires a mechanism called an artificial lift. This mechanism is useful for increasing the flow of fluids from a well. One that uses this method is the rod pump. The rod pump system needed the appropriate design (through the determination of the value of the parameters that affect) so that the pump runs optimally. But changing the appropriate design in real terms is not economically and time-efficient. The ideal rod pump system analysis procedure is to take downhole data (in the well) which is commonly called a pump card. A pump card calculation simulation is needed to efficiently analyze the rod pump system. The wave equation can describe the model of the rod pump system. A simulation of pump data calculation is performed using the finite difference method for the wave equation solution. Through the process of tuning parameter values using trial and error methods, the steps of tuning the parameter value of the rod pump system are proposed in this paper. For further research, a pump card calculation method based on a surface card can be developed to efficiently analyze the rod pump.